2016
DOI: 10.1002/mnfr.201600005
|View full text |Cite
|
Sign up to set email alerts
|

Organic honey supplementation reverses pesticide‐induced genotoxicity by modulating DNA damage response

Abstract: These results provide new insight regarding the effect of honey containing polyphenols on pesticide-induced DNA damage response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Malhomme de la Roche et al [15] found that ingestion of green tea protected PBMN cells challenged ex vivo with UV(A)/VIS (ultraviolet(A)/visible) radiation, but only in some subjects, described as responders. Alleva et al [16] gave a honey supplement to humans exposed to pesticides, and found, after two weeks’ supplementation, lower levels of EndoIII- and Fpg-sensitive sites in lymphocytes as well as an enhanced capacity for DNA repair. Dark chocolate induced a transient protection against H 2 O 2 -induced DNA damage in PBMN cells ex vivo [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malhomme de la Roche et al [15] found that ingestion of green tea protected PBMN cells challenged ex vivo with UV(A)/VIS (ultraviolet(A)/visible) radiation, but only in some subjects, described as responders. Alleva et al [16] gave a honey supplement to humans exposed to pesticides, and found, after two weeks’ supplementation, lower levels of EndoIII- and Fpg-sensitive sites in lymphocytes as well as an enhanced capacity for DNA repair. Dark chocolate induced a transient protection against H 2 O 2 -induced DNA damage in PBMN cells ex vivo [12].…”
Section: Resultsmentioning
confidence: 99%
“…In parallel experiments to their human honey trial, Alleva et al [16] showed that pre-treatment of cells with honey extract protected against pesticide-induced DNA damage and inhibition of DNA repair. Propolis extract (at high concentration) decreased the frequency of γ-ray-induced SBs in fibroblasts [50], and yet—at a much lower concentration—it caused oxidative damage (SBs measured with Fpg and EndoIII together in the comet assay) in a human cancer cell line, which was suppressed by antioxidants or catalase and so was imputed to the production of H 2 O 2 [51].…”
Section: Resultsmentioning
confidence: 99%
“…13; 2017 Table 1 summarizes the effect of honey and its derivatives on genome health in in vitro studies. Published articles claimed that honey, propolis and bee pollen can reduce the DNA damage induced by genotoxic agent such as benzo (α) pyrene (Russo et al, 2006), peroxynitrate (Luo et al, 2007), hydrogen peroxide (Afroz et al, 2016;Cheng et al, 2013;Habib et al, 2014;Sherin et al, 2015;Zhou et al, 2012), chlorpyrifos (pesticide) (Alleva et al, 2016) and tertiary-butyl-hydroperoxide (Turan et al, 2015). Generally, antioxidant can scavenge free radicals and reduce the potential of oxidative damage in the cell.…”
Section: Alves De Lima Et Al (2005)mentioning
confidence: 99%
“…Propolis also has a potential to increase the expression of DNA repair enzyme such as hOGG-1 and NEIL-1 (Turan et al, 2015). However, the protective effect by honey toward oxidative damage are mostly from flavonoid content in honey and its derivates (Alleva et al, 2016;Cheng et al, 2013Cheng et al, , 2017Russo et al, 2006;Sherin et al, 2015;Tsai et al, 2012). Propolis that contain flavonoid content such as galangin, pinochembrin, and chrysin have capability to reduce oxidative DNA damage thus become the one of beneficial factor of the propolis (Tsai et al, 2012).…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation